The effect of Aloe vera ethanol extract on the growth inhibition of Candida albicans - Via Karina Nabila; Imam Budi Putra (Medicinski glasnik, 2020)
Aim: Candida albicans can cause two major types of infections: superficial infections (such as oral or vaginal candidiasis) as well as life-threatening systemic infections, and Aloe vera extract is one of the potentially useful therapeutic options. The aim of this study was to determine antifungal properties of Aloe vera ethanol extract on vulvovaginal candidiasis caused by Candida albicans. Methods: Aloe vera ethanol extract was prepared by the maceration method with 70% ethanol and dissolved in DMSO into multiple concentrations (6.25%, 12.5%, 25%, and 50%). Candida albicans was cultured in Sabouraud dextrose agar for 72 hours and disc diffusion method was used to evaluate the inhibitory effect of each concentration in comparison with fluconazole. Zones of inhibition at 72 hours were measured and documented, then analysed to get the mean inhibition zone (MIZ). Results: After 72 hours, all concentrations of Aloe vera ethanol extract showed inhibition effect against C. albicans with mean inhibition zones of each concentration, 12.450±0.208 mm (6.25%), 13.975±0.457 mm (12.5%), 15.650±0.420 mm (25%), and 17.225±0.512 mm (50%), respectively. Fluconazole revealed comparable antifungal effect with MIZ of 11.025±0.478 mm. Oneway ANOVA test showed a significant effect of Aloe vera ethanol extract on inhibition zone of Candida albicans growth (p<0.005). Conclusion: Aloe vera ethanol extract possesses concentration dependent activity against Candida albicans that is comparable with standard antifungal agents.
Keywords: herbal; therapy; yeast infections